PENYELAMATAN EMBRIO Dendrobium anosmum Lindl. MELALUI KULTUR IN VITRO - Dewi, Putu Yuni Astriani; Astarini, Ida Ayu; Kriswiyanti, Eniek (Metamorfosa: Journal of Biological Sciences; Vol 3 No 2 (2016), 2016)
The aim of the research is to analyse germination percentage, effect of coconut water addition in the media to number of last stage embryos and development of final stage D. anosmum Lindl. embryo. Research was conducted at Plant Structure and Development of Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences University of Udayana and UPT. Balai Benih Induk Tanaman Pangan dan Hortikultura Provinsi Bali from February 2015 to July 2015. Three type of media were employed, i.e. PDA, Organic, MS. Three different concentration of coconut was added to media, i.e. 0 ml/L 50 ml/L, 100 ml/L. Results showed that seed D. anosmum Lindl. on PDA, Organic and MS has not germinated yet on all media, only swollen cells observed. Seed dormancy and maturity of seed were the main factors affecting seed germination.  Addition of 100 ml / L coconut water in MS showed that media is capable to increase the formation of final stages embryos (> 32 cells). Embryo development on PDA and Organic largely showed cell stage embryos 1 to 8 cells, while MS media already showed embryo development stages of > 32 cells.
Keywords: Plant Tissue Culture, Orchid, Germination, Murashige and Skoog, Embryo Growth, Proembryo